Shaping Love Through Contemplation According to St. Titus Brandsma OCarm (1881–1942) - Miczyński, Jan (Verbum Vitae, 2025)
The article is a theological-spiritual analysis of the teaching of St. Titus Brandsma (Anno Sjoerd Brandsma), a Dutch professor and martyr from Dachau, who lived in the years 1881–1942. This study seeks to show that in the Carmelite’s opinion, the contemplation (active and passive) of transcendent Love serves man in the formation of human love—for God, for people and for all creatures. In this way, mysticism does not alienate man, but introduces him to concrete reality, inspiring him to deep commitment and taking responsibility for himself and others. This is of particular importance in the ongoing spiritual battle between good and evil—individual and social. Seeing the dangers of the anti-human ideology of Nazism, Fr. Titus, seeing the dangers of the anti-human ideology of Nazism, tried to show contemplation as a way to return to the Truth and as a chance to save the human family. The analysis carried out in this study, focusing more on the substantive aspect of the writings and less on their chronology, makes it possible to discover the logic, coherence, and originality of Brandsma’s thought.